Biomechanical effects of hemin and sildenafil treatments on the aortic wall of chronic-hypoxic lambs - Navarrete, Álvaro; Inostroza, Matías; Utrera, Andrés; Bezmalinovic, Alejandro; González-Candia, Alejandro; Rivera, Eugenio; Godoy-Guzmán, Carlos; Herrera, Emilio A.; García-Herrera, Claudio (Frontiers in Bioengineering and Biotechnology, 2024)
Gestation under chronic hypoxia causes pulmonary hypertension, cardiovascular remodeling, and increased aortic stiffness in the offspring. To mitigate the neonatal cardiovascular risk, pharmacological treatments (such as hemin and sildenafil) have been proposed to improve pulmonary vasodilation. However, little is known about the effects of these treatments on the aorta. Therefore, we studied the effect of hemin and sildenafil treatments in the aorta of lambs gestated and raised at highlands, thereby subjected to chronic hypoxia. Several biomechanical tests were conducted in the descending thoracic aorta (DTA) and the distal abdominal aorta (DAA), assessing 3 groups of study of hypoxic animals: non-treated (Control) and treated either with hemin or sildenafil. Based on them, the stiffness level has been quantified in both zones, along with the physiological strain in the unloaded aortic duct. Furthermore, a morphological study by histology was conducted in the DTA. Biomechanical results indicate that treatments trigger an increment of axial pre-stress and circumferential residual stress levels in DTA and DAA of lambs exposed to high-altitude chronic hypoxia, which reveals a vasodilatation improvement along with an anti-hypertensive response under this characteristic environmental condition. In addition, histological findings do not reveal significant differences in either structure or microstructural content. The biomechanics approach emerges as a valuable study perspective, providing insights to explain the physiological mechanisms of vascular function. According to established results, alterations in the function of the aortic wall may not necessarily be explained by morphostructural changes, but rather by the characteristic mechanical state of the microstructural components that are part of the studied tissue. In this sense, the reported biomechanical changes are beneficial in mitigating the adverse effects of hypobaric hypoxia exposure during gestation and early postnatal life.